2021
DOI: 10.3390/medicina57050509
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Functional Effect of Thrombectomy on Patients with Middle Cerebral Artery Occlusion Who Exhibit Moderate to Severe Disability

Abstract: Background and Objectives: Endovascular thrombectomy (EVT is an emerging gold standard treatment for acute cerebral infarction and may allow functional improvement after subacute cerebral infarction. However, the long-term functional benefits of EVT in patients with moderate to severe disability remain unclear. We investigated the effects of EVT on the activities of daily living (ADL), handicap, gait, and eating in patients with middle cerebral artery (MCA) occlusion who exhibited moderate to severe disability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
(34 reference statements)
0
0
0
Order By: Relevance
“…These findings are congruent with Yi et al. (2021) who found that participants with moderate to severe disability at 2 weeks post ECR (mRS 3–5) exhibited moderate swallowing impairment (mean dysphagia outcome severity scale (O'Neil et al., 1999) (DOSS = 3) at 2 weeks, but recovered to mild swallowing impairment by 4 weeks (mean DOSS = 5) and on average were able to consume a regular diet by 6 months. The incidence of swallowing impairment in the current study was lower than Minchell et al.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These findings are congruent with Yi et al. (2021) who found that participants with moderate to severe disability at 2 weeks post ECR (mRS 3–5) exhibited moderate swallowing impairment (mean dysphagia outcome severity scale (O'Neil et al., 1999) (DOSS = 3) at 2 weeks, but recovered to mild swallowing impairment by 4 weeks (mean DOSS = 5) and on average were able to consume a regular diet by 6 months. The incidence of swallowing impairment in the current study was lower than Minchell et al.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast to language and cognitive performance, the incidence of swallowing impairment in the current study was only 24% at initial assessment (i.e., within 7 days of stroke and ECR) and all participants had recovered by the final assessment at 3 months. These findings are congruent with Yi et al (2021) who found that participants with moderate to severe disability at 2 weeks post ECR (mRS 3-5) exhibited moderate swallowing impairment (mean dysphagia outcome severity scale (O'Neil et al, 1999) (DOSS = 3) at 2 weeks, but recovered to mild swallowing impairment by 4 weeks (mean DOSS = 5) and on average were able to consume a regular diet by 6 months. The incidence of swallowing impairment in the current study was lower than Minchell et al (2022) who reported 64% of participants presented with dysphagia post ECR.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation